Application of MEPLWF: method performance evaluation of the Light Wood Frame construction system - Sotsek, Nicolle Christine; Leitner, Drielle Sanchez; Maceno, Marcell Mariano Corrêa; Marques, Marcos Augusto Mendes; Santos, Adriana de Paula Lacerda (Ambiente Construído, 2021)
One of the 17 Sustainable Development Goals (SDG) set out in this agenda, objective 11 is related to the search for more sustainable cities and communities. This study wishes to contribute in this effort, presenting a method application to evaluate the performance of light wood frame buildings in Brazil. The structure of the method used, named MEPLWF, is based on five dimensions, which involve criteria and sub-criteria that analyse technical, social, environmental and economic requirements to evaluate buildings. It allows the examination of the operating results of buildings and the discovery of performance-related problems. The proposed method was applied in a real case study in southern Brazil, during the pre-occupation phase of the building. As a result, the performance identified in the building was 94%, which is a high performance. The application of the method in this case study diagnosed points that should be reviewed by the construction company, such as items related to fire protection and safety, flexibility and adaptability of the building system, environmental plan, energy efficiency and Costs.